Social-mediated communication and network dynamics in online gambling discourse: a social network analysis of YouTube comments on “Indonesia Darurat Judi Online” - Atsilah Siregar, Jihan; Nugroho, Catur (Frontiers in Communication, 2025)
The research explores the dynamics of interaction and information distribution regarding the issue of online gambling in Indonesia through social media network analysis in the comment section of a YouTube video titled “Indonesia Darurat Judi Online,” uploaded by the tvOneNews.com channel. This research aims to identify critical actors, interaction patterns, and how information about online gambling is distributed among YouTube users. Drawing on social media network analysis (SNA), the study analyzes data collected from 3,673 unique user accounts and their corresponding comments and replies using Communalytic.org and analyzed using Gephi software. The results showed 3,110 nodes and 424 edges with a diameter value of 2, density of 0, reciprocity of 0, and centralization of 0.00001, depicting a decentralized communication network with minimal and one-way interactions. Key actors like @wanwan6171 and @diditsamodra have significantly influenced this network. These findings affirm the critical role of social media in disseminating information and shaping public opinion on complex social issues such as online gambling. This study highlights the limitations of social-mediated communication in fostering meaningful discussions on complex issues like online gambling. While social media serves as a platform for opinion expression, the lack of interaction suggests that it functions more as a broadcast medium rather than a deliberative public sphere. These insights can help policymakers and social media platforms design strategies for more effective digital discourse and online gambling awareness campaigns.